Effect of Omega-3 fatty acid added to parenteral nutrition on inflammatory in preterm infants - Tumer, Guzin; Mercanlıgil, Seyit Mehmet; Aygun Seren, Canan; Dağ, Ayhan (Progress in Nutrition, 2022)
Objective: This study aimed to investigate the effect of omega-3 fatty acid addition to Total Parenteral Nutrition (TPN) on the inflammatory process and clinical outcomes. Methods: The study included 51 infants who were in the Neonatal Intensive Care Unit (NICU) and fed by TPN for minimum 10 days, with a gestational age of ≤32 weeks and a birth weight of ≤2500 g. The preterm infants fed by TPN with 80% omega-9 and 20% omega-6 fatty acids were determined as Group 1(n:26) and by TPN with added omega-3 fatty acid (1.0g/day) as Group 2 (n:25). This retrospective study retrieved demographic characteristics, anthropometric measurements, nutrition therapy details, comorbidity development, inflammatory markers, and laboratory and clinical results from patient files. Those who received exchange transfusions and who received TPN for less than 10 days were excluded from the study. Results: Comorbidity developed in 35% of Group 1 and 28% of Group 2, with no difference between the groups (p < 0.05). There was no difference in gestational week at birth, birth weight, duration of mechanical ventilation (MV), duration of oxygen support, and maternal age between the two groups (p < 0.05). There was no difference in the carbohydrate (CH), protein and lipid levels, and glucose infusion rate (GIH) between the two groups (p <0.05). In Group 2, the daily amount of omega-3 fatty acid was increased by 1.0±0.1 g/day, accounting for 7.7±0.03% of the total energy. There was a significant decrease in the blood levels of Aspartate Aminotransferase (AST) and Total Bilirubin (T.Bil) on day 10 ​​in Group 2 (p < 0.05). Procalcitonin (PCT) significantly decreased on days 1, 4, 7, and 10 in both groups (p < 0.05). The difference in C-Reactive Protein (CRP) on days 4 and 10, and PCT and Neutrophil-to-Lymphocyte Ratio (NLR) on days 1, 4, 7, 10 was insignificant, with lower values in Group 2. Conclusion: The present study established a low level of positive changes in inflammatory findings and a decrease in liver function test results with the addition of fish oil to TPN. The different fatty acid contents of ILEs, the optimum ratio between the fatty acids, and the amount and duration of use affect the clinical outcomes. Further studies are needed to determine a safe, adequate dose and appropriate fatty acid profile.